2023
DOI: 10.3390/insects14020122
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Taxonomy Approach Reveals Cryptic Diversity within the Phoretic Pseudoscorpion Genus Lamprochernes (Pseudoscorpiones: Chernetidae)

Abstract: Pseudoscorpions represent an ancient, but homogeneous group of arachnids. The genus Lamprochernes comprises several morphologically similar species with wide and overlapping distributions. We implemented an integrative approach combining molecular barcoding (cox1), with cytogenetic and morphological analyses in order to assess species boundaries in European Lamprochernes populations. The results suggest ancient origins of Lamprochernes species accompanied by morphological stasis within the genus. Our integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 120 publications
2
17
0
Order By: Relevance
“…Ideally, other sources of evidence would be taken into account and the validation would be performed in an integrative framework (Carstens et al., 2013; Edwards & Knowles, 2014). Cytogenetics data (Řezáč et al., 2018; Štundlová et al., 2019), geometric morphometry (Christophoryová et al., 2023; Korba et al., 2022) and species distribution modelling (Newton et al., 2020; Stockman & Bond, 2007) were used for delineating taxa boundaries in morphologically homogeneous arachnids. Unfortunately, our final delimitation hypothesis does not allow statistical validation by the latter two methods, because the majority of the delimited taxa is composed of few individuals and singletons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ideally, other sources of evidence would be taken into account and the validation would be performed in an integrative framework (Carstens et al., 2013; Edwards & Knowles, 2014). Cytogenetics data (Řezáč et al., 2018; Štundlová et al., 2019), geometric morphometry (Christophoryová et al., 2023; Korba et al., 2022) and species distribution modelling (Newton et al., 2020; Stockman & Bond, 2007) were used for delineating taxa boundaries in morphologically homogeneous arachnids. Unfortunately, our final delimitation hypothesis does not allow statistical validation by the latter two methods, because the majority of the delimited taxa is composed of few individuals and singletons.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetics data (Řezáč et al, 2018; Štundlová et al, 2019), geometric morphometry (Christophoryová et al, 2023;Korba et al, 2022) and species distribution modelling (Newton et al, 2020;Stockman & Bond, 2007) (Arnedo & Ferrández, 2007) and the Chinese primitively segmented trapdoor spider Ganthela (Xu et al, 2018), but they also affect species distributions in vertebrates (Barrow et al, 2018;Soltis et al, 2006). The rivers play a particularly important role in the Southern Coastal Plain biodiversity hotspot, their changing course and local flooding created a system of patchy habitats that helped promote diversification in the region (Noss et al, 2015).…”
Section: How Many Species Of Cyclocosmia Are There?mentioning
confidence: 99%
See 1 more Smart Citation
“…Principally, three processes may lead to morphological crypsis [14]: (i) recent divergence, i.e., time since speciation was too short to allow morphological differentiation, (ii) morphological convergence, i.e., morphological similarity evolved independently among distantly related taxa in response to similar selection pressures, or (iii) morphological stasis, i.e., niche evolution and hence morphological differentiation across descendant species was constrained by selection (also known as the phylogenetic niche conservatism hypothesis). Christophoryová et al [15] estimated that cryptic Lamprochernes species diverged during the Oligocene era (approximately 31 Ma) and thus concluded that morphological stasis was the effective course. Morphological uniformity can challenge species delineation even if evolutionary distances are large, and traditional species diagnoses based on morphological characters may fail in such groups [16].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that even in central Europe, a region with a long tradition of faunistic and taxonomic research [17], the true species diversity of pseudoscorpions is not even roughly known. Studies involving DNA barcoding have demonstrated that currently accepted species often constitute complexes of cryptic species [15,[18][19][20]. This was most obvious in non-vagile, soil-dwelling representatives (Chthoniidae, Neobisiidae), with Neobisium carcinoides (Hermann, 1804) being the most prominent example.…”
Section: Introductionmentioning
confidence: 99%